Breed, Gender, and Age as Risk Factors for Canine Osteochondritis Dissecans - Slater, Margaret R.; Scarlett, Janet M.; Kaderly, R. E.; Bonnett, Brenda N. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
A retrospective case-control study of canine osteochondritis dissecans (OCD) was conducted using the hospital records at the New York State College of Veterinary Medicine between January 1980 and December 1987 and at the Ontario Veterinary College between January 1983 and June 1988. Information was collected on 208 cases and 416 controls. Breed, gender, and age (at onset of clinical signs and at diagnosis) were evaluated as risk factors for OCD of the shoulder, elbow, stifle, and hock using logistic regression. A distinct pattern of risk for large and giant breeds and certain ages emerged from the analysis for each joint. Males were more commonly affected than females only for the shoulder joint.
Keywords: Osteochondritis dissecans; dog; shoulder; elbow; stifle; hock; logistic regression